Kelas Peduli: Program Kolaboratif Guru dan Siswa dalam Meningkatkan Tanggung Jawab Siswa di Sekolah Dasar Kristen Arastamar Bone - Yoram H. A Tuan (Lembaga Pengembangan Kinerja Dosen, 2025)
This article discusses the implementation of the Caring Class program (Kelas Peduli) as a means of cultivating responsibility among elementary school students. The program is carried out through daily routines such as rotating clasroom duties, journaling, weekly class discussions, and positive reinforvement. A descriptive qualitative method with a participatory approach was used, involving both teachers and students in value hanituation. The results indicate that this program enhances students’awarenes of personal and sosial responsibility, strengthens discipline, and fosterscommunication and colaboration within the classroom community. Therefore , Kelas Peduli can be considered a best practice model for character aducation in elementary schools.